SERS Taper-Fiber Nanoprobe Modified by Gold Nanoparticles Wrapped with Ultrathin Alumina Film by Atomic Layer Deposition - Wenjie Xu; Zhenyi Chen; Na Chen; Heng Zhang; Shupeng Liu; Xinmao Hu; Jianxiang Wen; Tingyun Wang (Sensors, 2017)
A taper-fiber SERS nanoprobe modified by gold nanoparticles (Au-NPs) with ultrathin alumina layers was fabricated and its ability to perform remote Raman detection was demonstrated. The taper-fiber nanoprobe (TFNP) with a nanoscale tip size under 80 nm was made by heated pulling combined with the chemical etching method. The Au-NPs were deposited on the TFNP surface with the electrostatic self-assembly technology, and then the TFNP was wrapped with ultrathin alumina layers by the atomic layer deposition (ALD) technique. The results told us that with the increasing thickness of the alumina film, the Raman signals decreased. With approximately 1 nm alumina film, the remote detection limit for R6G aqueous solution reached 10−6 mol/L.